Relationship of Parents' Economic Conditions and Parenting Patterns with Children’s Development - Fadilla, Anisa Yuniar; Setyoboedi, Bagus (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: Each parent has its own parenting style in parenting which is usually influenced by the background they have, both in terms of education, socio-economics, work, customs and others. The purpose of this study was to analyze the relationship between the economic conditions of parents and parenting on the development of children.Methods: This type of research is quantitative research with a correlational research design. The sample in this study was all the population that met all the inclusion and exclusion criteria with a sampling technique using Total Sampling. The independent variable of this research is child development. The dependent variable studied in this study is the economic condition of parents and the intermediate variable in this study is parenting.Results: The results of this study indicate that there are 62.52% parents with middle economic conditions, 20.83% parents with poor economic conditions and 16.65% parents with affluent economic conditions. For parenting, it was found that 58.3% of parents used democratic parenting, 25% used permissive parenting and 16.7% of parents used authoritarian parenting. In child development, it was found that 70.8% of children had normal development and 29.2% of children had impaired development. The results of the Manova test on the relationship between parents' economic conditions and parenting patterns with child development showed a p-value of 0.650.Conclusion: The data shows that there is no significant relationship between the economic conditions of parents and parenting patterns with child development.